Pelatihan Desain Grafis Berbasis Canva untuk Meningkatkan Kreativitas Guru dalam Pengembangan Media Pembelajaran di SD 2 Pulau Kanalo 2 Kabupaten Sinjai - Jusman Jusman (Prodi PGSD Unsultra, 2026)
This community service activity aims to improve teacher creativity and competence in developing digital learning media through Canva-based graphic design training at SD 2 Pulau Kanalo 2, Sinjai Regency. The main challenge faced by the partners was teachers' limited ability to design engaging, innovative, and student-centered learning media. The activity's implementation method included planning, training implementation, mentoring, and evaluation. The training took the form of an interactive workshop that included an introduction to Canva, practical instructional media creation (educational posters, interactive presentations, and student worksheets), as well as discussions and feedback. All teachers at SD 2 Pulau Kanalo 2 participated in the activity. The results showed an increase in teachers' understanding and skills in using Canva as a graphic design tool for learning. Teachers were able to produce a variety of more creative, visual, and contextual learning media products. Furthermore, the training also increased teachers' motivation to utilize digital technology in the learning process. Therefore, Canva-based graphic design training is effective in supporting teacher professional development and contributing to improving the quality of learning in elementary schools, particularly in island regions.